2021
DOI: 10.3390/agronomy11102009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corn Stalks and Urea on N2O Production from Corn Field Soil

Abstract: Returning corn stalks to the field is an important and widely used soil management practice which is conducive to the sustainable development of agriculture. In this study, the effects of corn stalks and urea on N2O production in corn field soil were investigated through a 21-day incubation experiment. This study showed that increasing amounts of urea added to soil with a history of corn cultivation leads to increasing overall N2O emissions, by increasing both the intensity and the duration of emissions. Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Compared with urea application, corn stalks returning combined with urea application further increased NO3 --N by 45%, DOC by 53%, and DON by 122%, similar to Li et al (2021b). Corn stalks returning was considered to improve the physicochemical properties of soil (Chan et al 2002;Wu et al 2021). Wu et al (2022) also showed that straw returning could increase soil NO3 --N. The increase in NO3 --N, DOC, and DON may be due to the stimulation of extracellular enzyme activity by the addition of corn stalks (Chen et al 2014), and the decomposition of corn stalks releases macronutrients and changes nutrient availability (Devevre and Horwath 2000).…”
Section: Effects Of Corn Stalks Returning On Soil Physicochemical Pro...mentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with urea application, corn stalks returning combined with urea application further increased NO3 --N by 45%, DOC by 53%, and DON by 122%, similar to Li et al (2021b). Corn stalks returning was considered to improve the physicochemical properties of soil (Chan et al 2002;Wu et al 2021). Wu et al (2022) also showed that straw returning could increase soil NO3 --N. The increase in NO3 --N, DOC, and DON may be due to the stimulation of extracellular enzyme activity by the addition of corn stalks (Chen et al 2014), and the decomposition of corn stalks releases macronutrients and changes nutrient availability (Devevre and Horwath 2000).…”
Section: Effects Of Corn Stalks Returning On Soil Physicochemical Pro...mentioning
confidence: 99%
“…Soil organic matter and total N contents were determined by dry combustion of the samples using an Elemental Analyzer (Vario EL III, Hanau, Germany) (Yang et al 2017). Soil ammonium N (NH4 + -N) and nitrate nitrogen (NO3 -N) were extracted with 2 M KCl solution (Wu et al 2021), filtered, and analyzed with a continuous flow analyzer (AA3, Bran + Luebbe, Norderstedt, Germany). Soil pH was measured in a 1:2.5 soil/water suspension with a combination electrode (Yang et al 2017).…”
Section: Sample Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Straw contains a large amount of lignocellulose, soluble carbon, and other nutrient elements, and it has good porosity (Thíebeau et al 2021;Lu et al 2023). These characteristics of straw are often used to improve soil physicochemical properties, promote soil moisture and fertilizer retention, and ensure crop yield (Velthof et al 2002;Wu et al 2021). However, further clarification is needed regarding whether adding water retaining agents, inhibitors, and straw can promote corn production in this semi-arid cropland.…”
Section: Introductionmentioning
confidence: 99%
“…Following the various management recommendations (CE, ZW, IFS, ICM), many different initiatives were made to increase the value of this abundant and renewable agro-waste. The traditional "classic" valorization methods mostly recommended by ICM and IFS management strategies include the use of CS to prepare animal feed [20], as fuel [21], or as soil fertilizer [22]. The opportunities for CS valorization are expanded by the contemporary management strategies (CE, ZW).…”
Section: Introductionmentioning
confidence: 99%